Pengaruh Kompetensi Dosen, Motivasi dan Lingkungan Kampus terhadap Prestasi Belajar Mahasiswa : Studi Kasus pada Mahasiswa Reguler Angkatan 2022 Fakultas Ekonomi dan Bisnis Universitas Budi Luhur, Jakarta Selatan - Indah Fitriana; Widi Wahyudi (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to examine the influence of lecturer competence (X1), motivation (X2), and campus environment (X3) on students’ academic achievement (Y). The research focused on regular undergraduate students of the 2022 cohort at the Faculty of Economics and Business, Budi Luhur University, South Jakarta. A quantitative research design was applied, with data collected through questionnaires. The sampling technique employed was probability sampling with a simple random sampling approach, ensuring that each student had an equal chance of being selected as a respondent. A total of 86 valid responses were obtained. Data analysis consisted of descriptive analysis of the primary data and inferential analysis using multiple linear regression with the aid of SPSS version 22. The regression equation obtained was Y = 3.829 + 0.584X1 + 0.561X2 + 0.134X3 + €. The findings indicate that lecturer competence has a positive and significant effect on students’ academic achievement, implying that higher lecturer competence contributes to better student learning outcomes. Motivation also shows a positive and significant influence, highlighting that strong learning motivation plays a crucial role in improving academic performance. Meanwhile, the campus environment has a positive but not significant effect, suggesting that although the learning environment contributes to student achievement, its impact is not substantial when compared to other variables. Overall, the results underscore the importance of enhancing lecturer competence and fostering student motivation as key strategies for improving academic achievement, while also considering the campus environment as a supporting factor for student success.